Coordination mechanism of the three-echelon supply chain of fresh agriproduct with joint efforts - Wu, Jun; Jia, Wenpeng; Ba, Yile; Liu, Xin; Zhang, Yunbo; Li, Jian (Frontiers in Sustainable Food Systems, 2023)
Nowadays the freshness level of agricultural products has become one of the major concerns for consumers. The demand for fresh agricultural products in the market has been increasing more than ever. However, the circulation losses of fresh agricultural products has been very considerable during the logistic processes, such as long-distance transportation. Statistics shows there are 20%-25% perishable agri-products become deterioration in the circulation loop in developing countries while that of developed countries in this regard can be controlled lower than 5%. It is necessary for developing countries to improve their cold chain logistics and reduce post-production losses of this kind of agri-products. Freshness-keeping effort to fresh agricultural products and the coordination mechanism of the supply chain have become two of the hot topics in this field. Based on the existing research, this paper describes freshness-keeping effort as a joint effort function of the supplier and the manufacturer, and studies the optimization and coordination of a three-echelon fresh agricultural products supply chain. Three decision-making modes are modeled in this research, including decentralized decision-making, centralized decision-making, and collaborative decision-making. Then four scenarios under the three decision-making modes are analyzed, and the profit distribution of two cooperative modes and centralized decision-making mode is calculated using the average tree solution. The author finds that different cooperation style of enterprises in the agri-product supply chain has different impact on the freshness level of the final product got by consumers. Both the final freshness level and the price of the product depend on the joint freshness-keeping effort of the supplier and the manufacturer. The cooperation of enterprises in the three-echelon supply chain is conducive to the improvement of the final freshness level of agri-products and the maximization of the supply chain’s total profit. In such a three-echelon fresh agri-products supply chain, the use of average tree solution can effectively distribute the profits and promote the cooperation among different parties.